2020
DOI: 10.3390/ijms21041542
|View full text |Cite
|
Sign up to set email alerts
|

Acetate and Butyrate Improve β-cell Metabolism and Mitochondrial Respiration under Oxidative Stress

Abstract: Islet dysfunction mediated by oxidative and mitochondrial stress contributes to the development of type 1 and 2 diabetes. Acetate and butyrate, produced by gut microbiota via fermentation, have been shown to protect against oxidative and mitochondrial stress in many cell types, but their effect on pancreatic β-cell metabolism has not been studied. Here, human islets and the mouse insulinoma cell line MIN6 were pre-incubated with 1, 2, and 4 mM of acetate or butyrate with and without exposure to the apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 53 publications
3
79
1
2
Order By: Relevance
“…Microbial fermentation of prebiotics generates short-chain fatty acids (SCFA), such as acetate and butyrate, that have been shown to protect against oxidative and mitochondrial stress [ 47 ], enhance gut barrier, increase glucangon-like peptide 1 and 2 (GLP-1 and GLP-2) secretion [ 48 ], which delay gastric emptying and induce satiety [ 49 ]. Besides, incretins reduce hepatic expression of inflammatory and oxidative stress markers during obesity and diabetes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial fermentation of prebiotics generates short-chain fatty acids (SCFA), such as acetate and butyrate, that have been shown to protect against oxidative and mitochondrial stress [ 47 ], enhance gut barrier, increase glucangon-like peptide 1 and 2 (GLP-1 and GLP-2) secretion [ 48 ], which delay gastric emptying and induce satiety [ 49 ]. Besides, incretins reduce hepatic expression of inflammatory and oxidative stress markers during obesity and diabetes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, SCFA inhibits lipolysis and reduces inflammation, enhancing energy metabolism regulation [ 16 ]. A recent study showed that SCFAs enhanced the viability of islets and β-cells, prevented STZ-induced cell apoptosis, viability reduction, mitochondrial dysfunction, and the overproduction of reactive oxygen species (ROS) and nitric oxide (NO) [ 47 ]. Mechanisms responsible for the efficacy of dietary n-3 PUFAs include reduction in IFN-γ, IL-17, IL-6, and TNF-α corroborating our findings (reduction in TNF-α) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these rescuing effects, SCFAs prevented the downregulation of the mitochondrial fusion genes Mfn1, Mfn2 and Opa1 and the upregulation of the fission genes Drp1 and Fis1 during STZ exposure. Acetate revealed more efficiency in inhibiting the ROS and increasing the metabolism, while butyrate had a weaker effect but was stronger in inhibiting NO generation and the SCFA receptor GPR41 [101].…”
Section: Scfas Secondary Bile Acids and Mitochondriamentioning
confidence: 95%
“…Notably, Mollica et al showed that sodium butyrate reduced ROS production and ameliorated mitochondrial function in the livers of insulin-resistant obese mice [100]. Similarly, Shuxian et al revealed that both acetate and butyrate can prevent mitochondrial dysfunction and reduce oxidative and nitrosative stresses in human islets and β cells after exposure to the apoptosis inducer and metabolic stressor streptozotocin (STZ) [101]. In addition to these rescuing effects, SCFAs prevented the downregulation of the mitochondrial fusion genes Mfn1, Mfn2 and Opa1 and the upregulation of the fission genes Drp1 and Fis1 during STZ exposure.…”
Section: Scfas Secondary Bile Acids and Mitochondriamentioning
confidence: 99%
“…Some studies have been conducted to examine the relationship between SCFAs, and energy metabolism and immune regulation (D'souza et al 2017;Hu et al 2018). These studies show that, compared to other SCFAs, butyrate has more significant lipid-lowering, antioxidant, and insulin resistance-improving effects, and has been used to prevent a variety of inflammatory diseases (Li et al 2019;Hu et al 2020). In the present article, we discuss the beneficial effects of butyrate on several processes involved in the occurrence and development of AS.…”
Section: Introductionmentioning
confidence: 99%